Long-term Survival and Cost-effectiveness Associated With Axicabtagene Ciloleucel vs Chemotherapy for Treatment of B-Cell Lymphoma - Whittington, Melanie D. (JAMA Netw Open, 2019)
IMPORTANCE: Axicabtagene ciloleucel, a chimeric antigen receptor T-cell therapy, represents a new and potentially curative treatment option for B-cell lymphoma. It is expected to have long-term survival benefits; however, long-term survival data are limited. OBJECTIVE: To estimate the long-term survival and cost-effectiveness of axicabtagene ciloleucel for treatment of relapsed or refractory B-cell lymphoma. DESIGN, SETTING, AND PARTICIPANTS: Economic evaluation study using a survival analysis that digitized and extrapolated survival curves published in the ZUMA-1 trial (Safety and Efficacy of KTE-C19 in Adults With Refractory Aggressive Non-Hodgkin Lymphoma), which enrolled patients between November 2015 and September 2016 and had a maximum follow-up of 24 months. Five different survival models (standard parametric, flexible parametric, 2 mixture cure models, and a flexible parametric mixture model) were used to extrapolate the survival curves to a lifetime horizon from January through June 2018. A cost-effectiveness analysis, from both a trial-based and lifetime horizon, was also conducted to inform the value of this novel therapy. The model was based on data from 111 patients with B-cell lymphoma who were enrolled in the ZUMA-1 trial. INTERVENTIONS: One-time administration of axicabtagene ciloleucel compared with chemotherapy. MAIN OUTCOMES AND MEASURES: Undiscounted and discounted life-years (LYs) and quality-adjusted life-years (QALYs), total costs, and incremental costs per LY and QALY gained. RESULTS: The modeled cohort of 111 patients started at 58 years of age. At the end of the trial, treatment with axicabtagene ciloleucel resulted in 0.48 more LYs and 0.34 more QALYs than chemotherapy, producing a cost-effectiveness estimate of $896 600 per QALY for public payers and $1 615 000 per QALY for commercial payers. Extrapolated long-term survival for patients treated with axicabtagene ciloleucel ranged from 2.83 to 9.19 discounted LYs and from 2.07 to 7.62 discounted QALYs. Incrementally, treatment with axicabtagene ciloleucel was associated with 1.89 to 5.82 discounted LYs and 1.52 to 4.90 discounted QALYs vs chemotherapy. With the use of these incremental estimates of survival, cost-effectiveness estimates ranged from $82 400 to $230 900 per QALY gained for public payers and from $100 400 to $289 000 per QALY gained for commercial payers. CONCLUSIONS AND RELEVANCE: Treatment with axicabtagene ciloleucel appears to be associated with incremental gains in survival over chemotherapy. The range in projected long-term survival was wide and reflected uncertainty owing to limited follow-up data. Cost-effectiveness is associated with long-term survival, with further evidence needed to reduce uncertainty.